RECENT ORNITHOLOGICAL EXPEDITIONS TO SIBERUT ISLAND, MT. TALAMAU AND RIMBO PANTI NATURE RESERVE, SUMATRA, INDONESIA - Tri Haryoko; Oscar Johnson; Matthew L. Brady; , Subir B. Shakya; M. Irham; Yohanna Yohanna; Rusdiyan P. Ritonga; Dewi M. Prawiradilaga; Frederick H. Sheldon (Treubia, 2020)
Siberut Island, Mt. Talamau, Rimbo Panti Nature Reserve, and intervening locations in West Sumatra Province were visited during two expeditions in 2018-2019 by ornithologists from the Museum Zoologicum Bogoriense (MZB) - Indonesian Institute of Sciences (LIPI), Louisiana State University Museum of Natural Science (LSUMNS), and Andalas University. The main objective of these expeditions was to obtain data and tissue-subsample rich museum specimens for morphological and genetic studies of phylogeny and population genetics of Southeast Asian birds aimed at understanding the causes of avian diversification in the region. We also observed, photographed, and audio-recorded numerous bird species during the expeditions and archived these data. In total, 285 species were identified, and specimen material was collected from 13 species and 26 subspecies not previously represented in tissue resource collections. Here, we provide complete lists of birds found at each location, highlight distributional discoveries, and note cases of potential taxonomic, ecological, and conservation interest.